2020
DOI: 10.1088/1755-1315/604/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Improving taxation of agricultural production as a factor of successful development of the agricultural sector in Russia

Abstract: Modern reality, the current economic situation in the world put forward special requirements for ensuring the food security of the state, and conducting import substitution. The purpose of the study is to identify the advantages and disadvantages of the taxation system of agricultural producers in the form of unified agricultural tax, the impact of changes made to the Tax Code. The study used general methods of cognition (deduction and induction, analysis and synthesis, observation method, generalization and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In addition, the intensification and growth of entrepreneurial activity in the agricultural sector contribute to improving the standard and quality of life of the rural population. [7] The study identified deficiencies in the single agricultural tax, such as: -low interest of taxpayers in its application; -The need for constant monitoring of income from the sale of agricultural products so that it does not exceed 70 per cent of total income; -Unlike the general tax regime, in which the list of expenses is open, while under a single agricultural tax -closed; -loss of part of the market in the conditions of interest of large processing enterprises and retail chains in VAT (before making corresponding changes); -The special tax regime in the form of a single agricultural tax is not sufficiently flexible and therefore it is not possible to regulate certain processes in the productive sector; the main goal of introducing a single agricultural tax is to increase the investment attractiveness of agricultural production.…”
Section: Results Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the intensification and growth of entrepreneurial activity in the agricultural sector contribute to improving the standard and quality of life of the rural population. [7] The study identified deficiencies in the single agricultural tax, such as: -low interest of taxpayers in its application; -The need for constant monitoring of income from the sale of agricultural products so that it does not exceed 70 per cent of total income; -Unlike the general tax regime, in which the list of expenses is open, while under a single agricultural tax -closed; -loss of part of the market in the conditions of interest of large processing enterprises and retail chains in VAT (before making corresponding changes); -The special tax regime in the form of a single agricultural tax is not sufficiently flexible and therefore it is not possible to regulate certain processes in the productive sector; the main goal of introducing a single agricultural tax is to increase the investment attractiveness of agricultural production.…”
Section: Results Of the Researchmentioning
confidence: 99%
“…It is proposed to abolish the exemption from value added taxes of all payers of a single agricultural tax, regardless of their income, and use the indicator. [7]…”
Section: Introductionmentioning
confidence: 99%
“…In the modern conditions of the development of the Russian economy, the issue of food security of the country comes to the fore, and the strategy of agricultural development should be focused on the self-sufficiency of the regions and the country as a whole. However, the existence of a separate, and even more so a wide range of types of state support for agricultural production requires a significant and national regulatory framework [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this method is widely used, in conjunction with the implementation of targeted subsidies and other budgetary mechanisms for state assistance in the agricultural sector. In the tax framework of industrialized nations, agriculture often incurs both national taxes, such as corporate income tax and value added tax, as well as municipal taxes, including land and agricultural taxes (Zotikov, N., Savderova, A., & Lyubovtseva, E. 2020).…”
Section: Literature Reviewmentioning
confidence: 99%